Maternal neutralizing antibodies against a CRF01_AE primary isolate are associated with a low rate of intrapartum HIV-1 transmission - Samleerat T. (2014)
Mother-to-child transmission (MTCT) of HIV-1 provides a model for studying the role of passively acquired antibodies in preventing HIV infection. We determined the titers of neutralizing antibodies (NAbs) against six primary isolates of clades B and CRF01_AE in sera from 45 transmitting and 45 nontransmitting mothers matched for the main independent factors associated with MTCT in Thailand. A lower risk of MTCT, particularly for intrapartum transmission, was associated only with higher NAb titers against the CRF01_AE strain, MBA. The envelope glycoprotein of this strain showed an unusually long V2 domain of 63 amino acids, encoding six potential N-linked glycosylation sites. We provided experimental data indicating that the extended V2 domain contributed to the higher level of resistance to neutralization by mothers' sera in this strain. Taken together the data suggest that some primary isolates with specific properties may be useful indicators for identifying protective antibodies. © 2009 Elsevier Inc. All rights reserved.